Malachiasz Kramski komendarz kościoła w Nowym Kramsku (przeł. XVII i XVIII w.) = Malachi Kramski, commendarius of the church in Nowe Kramsko (turn of the 18th century) - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article ?Malachi Kramski, commendarius of the church in Nowe Kramsko (turn of the 18th century)? describes pastoral and organizational activity of Malachi, a Cistercian from the Obra abbey, in the parish of Nowe Kramsko. Malachi was a professor of theology and one of the most outstanding Cistercian writers of 18th century Poland. Between 1697 and 1721, he served as a commendarius of the church in Nowe Kramsko. His activities in the parish were documented in the Chronicle of the Parish in Nowe Kramsko kept since the 17th century.
Keywords: Malachiasz Kramski; Nowe Kramsko (pow. babimojski); historia kościoła; The Malachi of Kramsko; history of church